Challenges inhibiting Islamic banking growth in Indonesia using the Analytical Hierarchy Process - Iswanaji, Chaidir (Journal of Islamic Economics Lariba, 2018)
The banking sector has an essential role in supporting economic growth in the world. Islamic banking has become an increasingly popular method for reducing poverty, financial inclusion and economic development. Its existence is needed in developing countries like Indonesia. The purpose of this study is to identify and prioritize challenges that hinder the growth of Islamic banking in Indonesia. The study was conducted in two stages: the first stage of investigating the challenges in the sharia banking industry in Indonesia. The second phase identifies and determines the priority challenges that hinder the growth of sharia banking using Analytical Hierarchy Process (AHP). The results reveal that the biggest challenge is the regulatory framework. Islamic banking requires favorable government policies and regulations and a positive effect on Islamic banking. Government policies to expand the market share of Islamic banking is one of the priority to be done soon. The second challenge is the lack of qualified human resources. Human resources in Islamic banking should be knowledgeable both sharia law and economics. Hence, providing qualified human resources need specialized education institutions concerning in Islamic finance. The third challenge is the lack of awareness of Islamic banking even in a Muslim community. They have a less understanding about the terms, products, and also Islamic principles of Islamic banking.